UTANG LUAR NEGERI; PARADOKS PEMBANGUNAN EKONOMI INDONESIA - Pellu, Arifin (IAIN Ambon, 2019)
This article aims to look at the relevance of Indonesia's foreign debt with its contribution to development accompanied by a study of sharia economics on debt. The amount of Indonesia's foreign debt continues to swell. Government savings that are expected to reduce the burden of external debt cannot reduce the burden of external debt. In fact, it has even added to the burden of external debt to penetrate Rp5,410 trillion. Indonesia is one of the countries that still rely on foreign aid to fund development, whether through loans or debt or foreign grants. The government does not have a strong commitment to pay off foreign debt. Instead of paying off, the government is diligently adding new debt without paying attention to the balance (balance) balance of payments. The development process carried out is the process of